1989
DOI: 10.1063/1.344040
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of the influence of oxygen partial pressure on the incorporation of residual silicon impurities in vapor-phase epitaxial gallium arsenide

Abstract: Dynamic study of the surfaces of (001) gallium arsenide in metal-organic vapor-phase epitaxy during arsenic desorption

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The Hall measurement also indicates an n‐type carrier concentration of 4.0·10 16 cm −3 in GaP grown on SI‐GaAs, due to an unintentional incorporation of Si caused by the reaction of HCl and the quartz reactor wall. It was reported that Si incorporation can be suppressed in HVPE‐grown GaAs by injecting O 2 over molten Ga . To enhance the purity of GaP, injection of O 2 during HVPE growth is a promising approach and worth the attention in future research.…”
Section: Resultsmentioning
confidence: 99%
“…The Hall measurement also indicates an n‐type carrier concentration of 4.0·10 16 cm −3 in GaP grown on SI‐GaAs, due to an unintentional incorporation of Si caused by the reaction of HCl and the quartz reactor wall. It was reported that Si incorporation can be suppressed in HVPE‐grown GaAs by injecting O 2 over molten Ga . To enhance the purity of GaP, injection of O 2 during HVPE growth is a promising approach and worth the attention in future research.…”
Section: Resultsmentioning
confidence: 99%